TELAAH TERHADAP PANDUAN RANCANG KOTA, KAWASAN PONDOK INDAH: SUB KAWASAN DI RUAS 1 - Ariaji, Priscilla Epifania; Salim, Justine; Horis, Ivonne Nelvina; Sutrisno, Jennifer (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2024)
The dynamic changes and development of Jakarta have actually been considered and anticipated through the creation of Urban Design Guidelines (UDGL), which are usually evaluated every five years. Pondok Indah area is one of the areas that holds significance in its development in the southern part of Jakarta and already has the Pondok Indah Area Urban Design Guidelines, last revised in 2012. This PKM (Community Service Program) aims to contribute by participating in the evaluation of the implementation of existing Urban Design Guidelines in Jakarta. The focus of observation taken from the UDGL is the Pondok Indah Area UDGL established by Governor Regulation number 185 of 2012. The area's vision as an integrated business center serving domestic and international businesses needs to be assessed for its development. The evaluation of the Pondok Indah Area UDGL will be divided into three PKM proposals focusing on sub-areas in Sections 1, 2, and 3. This proposal will focus on the sub-area in Section 1. The method used is descriptive-analytical-comparative, comparing government plans outlined in the UDGL with actual conditions in the field. Data collection is conducted through literature review and field surveys, followed by a comparative analysis method, evaluating the actual occurrences to draw conclusions. The main questions focus on